Strategic management of public diplomacy digital communication: A literature review - Skočajić, Ivana; Petrović, Dejan (Industrija, 2023)
Public diplomacy has been gaining a more significant role in national diplomatic relations, which has been instigated with greater usage of new technologies and digital media and expansion of online communication of government institutions with international public. Within the contemporary environment, the character of public diplomacy has changed and the essence of public diplomacy has moved from one-way and state-centered communication perspective towards an interactive, relationship building and fostering perspective. In order to enable reaching of foreign policy goals, public diplomacy demands strategic approach to communication, especially when it comes to digital channels such as social media. Important topics related to public diplomacy should be referred to as strategic issues in digital communication, which could represent either problems or opportunities for diplomatic institutions and individuals, and, therefore, should be approached from the perspective of strategic issue management. The aim of this paper is to improve the understanding of the public diplomacy digital communication from the strategic issues management perspective by providing a comprehensive literature review on this topic, and to provide basis for further empirical research.